Half a Century of Economic and Social Development Policies of the UN and Bretton Woods Institutions (The Iqbal Memorial Lecture) (The Pakistan Development Review, 1995)
It is customary to date the origin of the Bretton Woods system back to 1942 when Keynes, and his associates in London, prepared the three famous memoranda on the International Clearing Union, on Commodity Buffer Stocks and Plans for Relief and Reconstruction. To these three memoranda we may add the Beveridge Report which appeared in the same year, 1942. Keynes had taken a great interest in the Beveridge Report and this model of a national social welfare state was readily capable of international extension and application. However, in this historical perspective, we may well go a little further back. The Great Depression of the 1930s had shown that in the absence of multilateral agreements and multilateral institutions, the economic system was in danger of degenerating into beggar-my-neighbour policies leading to general immiserisation. The World Economic Conference of 1931 had been a first attempt to create an international economic order to prevent this condition from continuing. Although this attempt ended in failure, yet the ideas then brought forward had continued to reverberate in Keynes’s mind. His vision underlying the 1942 documents was governed by the overarching principle of “Never Again!” -never again back to the conditions of the 1930s which were seen as having brought about not only mass misery and mass unemployment but also Hitlerism and war. Also never again a failure like that of the 1931 World Economic Conference!